Iterative compression and exact algorithms - Fomin, Fedor V.; Gaspers, Serge; Kratsch, Dieter; Liedloff, Mathieu; Saurabh, Saket (Theoretical computer science, 2010)
Iterative compression has recently led to a number of breakthroughs in parameterized complexity. Here, we show that the technique can also be useful in the design of exact exponential time algorithms to solve NP-hard problems. We exemplify our findings with algorithms for the Maximum Independent Set problem, a parameterized and a counting version of d - Hitting Set and the Maximum Induced Cluster Subgraph problem.